2017
DOI: 10.1016/j.cub.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Ionotropic Receptors Mediate Drosophila Oviposition Preference through Sour Gustatory Receptor Neurons

Abstract: Summary Carboxylic acids are present in many foods, being especially abundant in fruits. Yet, relatively little is known about how acids are detected by the gustatory systems, whether they have a potential role in nutrition or provide other health benefits. Here, we identify sour gustatory receptor neurons (GRNs) in tarsal taste sensilla of Drosophila melanogaster. We find that most tarsal sensilla harbor a sour GRN that is specifically activated by carboxylic and mineral acids, but does not respond to sweet a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
132
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(139 citation statements)
references
References 53 publications
7
132
0
Order By: Relevance
“…One gram of frass from caterpillars raised on either D. wrightii or N. attenuata were put into a 500-mL plastic container. A circular filter paper (diameter: 12 mm Whatman, Sigma-Aldrich USA) loaded with 10 µL of diluted bromodecane (1:10 4 in hexane) was used as an internal standard. Through a hole in the lid of the container, a SPME fiber (50 µm Divinylbenzene / Carboxen / Polydimethylsiloxane coating; Supelco) was exposed to the container headspace for 30 min at room temperature without agitation, and then introduced into the injector inlet for 2 min at 250°C in split-less mode.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One gram of frass from caterpillars raised on either D. wrightii or N. attenuata were put into a 500-mL plastic container. A circular filter paper (diameter: 12 mm Whatman, Sigma-Aldrich USA) loaded with 10 µL of diluted bromodecane (1:10 4 in hexane) was used as an internal standard. Through a hole in the lid of the container, a SPME fiber (50 µm Divinylbenzene / Carboxen / Polydimethylsiloxane coating; Supelco) was exposed to the container headspace for 30 min at room temperature without agitation, and then introduced into the injector inlet for 2 min at 250°C in split-less mode.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, gravid females must carefully examine the environment prior to selecting the oviposition site. For this, they utilize visual 1, 2 , gustatory 3, 4 , mechanosensory 5 , as well as olfactory 6, 7 cues. Among these modalities, olfaction plays a pivotal role in an insect’s life, as it provides information not only about oviposition sites but also about other biologically relevant resources such as food and mating partners 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, transcriptomic and in situ expression analyses in a range of animals indicate that Ir genes are expressed in peripheral, rather than central, neurons [5][6][7][8][9]. Functional analyses of IRs, in particular in Drosophila melanogaster, have shown that these receptors have diverse roles in environmental sensing, including in olfaction [6,[10][11][12], gustation [13][14][15][16][17][18][19][20][21], hygrosensation [22][23][24] and thermosensation [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these compounds are acids, which exist widely in nature as common products of plants [5,6]. In Drosophila , acetic acid is sensed to assess food, oviposition medium, and mating [710]. Many other insect species, including armyworms, can be trapped by acetic acid-containing lures [1115].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Ir75a is also used by D. melanogaster and D. sechellia to smell acetic acid and propionic acid [29,30]. Ir76b mediates oviposition preference in female Drosophila by sensing acetic acid and citric acid through gustatory reception [10]. Meanwhile, reports on lepidopteran species have also revealed glomeruli based coding for feeding behaviors which were elicited by acidity components [31].…”
Section: Introductionmentioning
confidence: 99%